The correlation of obesity, smoking, fried foods consumption pattern and food intake with lipid profile in civil servant in Yogyakarta, Indonesia - Sudargo, Toto; Sari, Fahmi Tiara; Naomi, Novita Dian (International Journal Of Community Medicine And Public Health, 2017)
Background: Dyslipidemia is an abnormal change in the levels of lipid profile such as increased levels of total cholesterol, LDL, triglycerides or decreased levels of HDL. The proportion of the Indonesian population (> 15 years old) with a total cholesterol level above the normal value amounted to 35,9%. Objective: To determine the correlation of obesity, smoking, fried food consumption pattern and food intake with lipid profile in civil servant in Yogyakarta. Methods: This study is an observational study with cross sectional design at employees of Gadjah Mada University who perform medical check-up at the GMC-Health Center Yogyakarta. There are 179 respondents in the study. Subjects are categorized to have dyslipidemia (based on NCEP ATP III criteria) if it meets ≥ 1 of the following criteria: (1) Total cholesterol ≥ 200 mg/dL; (2) LDL cholesterol ≥ 130 mg / dL; (3) HDL cholesterol < 40 mg / dL; and (4) Triglycerides ≥150 mg / dL. Fried food consumption patterns and food intake is obtained using semi-quantitative food frequency questionnaire (SQ-FFQ). Data were analyzed by Chi Square, Independent t test and Mann Whitney test (adjusted for scale variables used) with a confidence level of 95%. Results: One hundred and fifty five of 179 respondents (87.3%) diagnosed with dyslipidemia. There are 52% abnormal cholesterol, abnormal LDL 67%, 43% and 28.5% with abnormal HDL and abnormal triglycerides, respectively. The statistical test showed the correlation of obesity (p=0,022), smoking (p=0,013), the type of fried food (p=0.047), the amount of fried foods (p=0,013) and fat intake from fried foods (p=0.036) has significant association with lipid profile levels. Conclusions: There is significant correlation between obesity, smoking, type of fried food, amount of fried foods and fat intake from fried food with lipid profile levels.